2022
DOI: 10.1155/2022/3688596
|View full text |Cite
|
Sign up to set email alerts
|

Design and Research of VR Basketball Teaching System Based on Embedded Intelligent Sensor

Abstract: Physical education pedagogy serves as a carrier of physical education theory and practical activities and plays an important role in physical education. The reform and development of education are always related closely to the growth of scientific and technological development, and people’s physical education training methods are also undergoing subtle changes. The traditional single and formulaic training methods in the past have gradually turned to modern training methods with better interaction and visibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
1
0
0
Order By: Relevance
“…Therefore, there is a need for monitoring and analyzing the psychological attitude of athletes in order to improve their future performance ( Lochbaum et al, 2021 , 2022 ; Zhou, 2021 ). Virtual basketball training is more interactive, visual, targeted and effective ( Jiang et al, 2022 ), which is also confirmed by the results of this study.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, there is a need for monitoring and analyzing the psychological attitude of athletes in order to improve their future performance ( Lochbaum et al, 2021 , 2022 ; Zhou, 2021 ). Virtual basketball training is more interactive, visual, targeted and effective ( Jiang et al, 2022 ), which is also confirmed by the results of this study.…”
Section: Discussionsupporting
confidence: 86%
“…Artificial and virtual reality technologies offer immersive training experiences that allow players to simulate game scenarios and practice decision-making in a controlled environment (Pagé et al, 2019;Richard et al, 2022;Song, 2021). By analyzing their movements, field awareness and tactical choices, players can bridge the gap between training sessions and real games (Jiang & Zhang, 2022;Soltani & Morice, 2023).…”
Section: Artificial and Virtual Reality -Artificial Intelligencementioning
confidence: 99%
“…Teaching sports movements is closely linked to new educational methods and technology. Traditional methods of physical training have given way to modern approaches, which have prompted trainers and physical training experts to develop new training methods and modes (8). "The use of modern technologies in teaching and learning has become increasingly important, and video modeling has proven to be an effective method for teaching various movement skills, including demonstrating a skilled model to athletes.…”
Section: Introductionmentioning
confidence: 99%